Analisis Fungsi Pajak dalam Negara Modern Berdasarkan Perspektif Ekonomi Islam - Nessa Maulidhyna; Zanatull Cahya (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
Taxes are the main fiscal instrument in modern states, serving various strategic functions such as budgeting, regulation, stability, and income redistribution. Taxes are not only a source of state revenue but also a tool to encourage economic growth and the equitable distribution of welfare. In the context of Islamic economics, taxes have a different position but are not fundamentally contradictory. Islam recognizes the concept of levies such as zakat, kharaj, jizyah, and ushr, which have similar objectives to modern taxes, namely for the welfare and social justice. This research uses a qualitative method with a literature study approach to analyze the alignment between the function of taxes in modern states and the principles of Islamic economics. Data were collected through a literature review from relevant academic sources. The research results show that although there are differences in mechanisms and characteristics, there is a common ground in the main goal, which is the welfare of society. Taxes can be accepted in Islamic economics as long as they are collected fairly, transparently, proportionally, and used for the public good. Further analysis indicates that the principles of maqashid sharia can serve as an important reference in modern tax reform to better align with Islamic values. The conclusion of this study emphasizes the importance of integrating Islamic economic principles into the tax system to create social justice, fiscal efficiency, and sustainable development. This research is expected to provide theoretical and practical contributions to the development of a tax system based on Sharia values in the contemporary era.